The canonical connection of motor skills and performance of technical elements of goal shooting in water polo - Nurkovic, N.; Imamovic-Turkovic, D.; Mirvic, E. (Sportski Logos, 2021)
The main goal of this research is to determine and explain the connection between motor skills and the performance of technical elements of goal shooting in a water polo game. The sample includes 80 water polo players from Water Polo Clubs Sarajevo City Club, Varepolo Club Torpedo, Water Polo Club Akademija, and Water Polo Club Dabar. The testing included a sample of 80 water polo players, registered in Bosnian-Herzegovinian clubs. The determination of the level of basic motor abilities was performed using measuring instruments. Movement structuring mechanism: Air maneuverability (MOKZ), Hand taping (MTAP), Foot taping (MTAN), The synergistic-tone and tone control mechanism: Deep bench press (MDPK), Leaning with reach in sitting (MSJED), Transverse standing on the beam (MGRED), Excitation intensity control mechanism: Running at 20m - flying start (M20M), Triple jump from the place (MTRS), Long jump from the place (MDALJ), Excitation duration control mechanism: Hinge height (MVZG), Hull lift in 30 seconds (MDT30 ), Push-ups (MSKL). The sample of variables for assessing the performance of technical elements of shooting on goal in a water polo game - Shot accuracy test: Shooting from the left wing from a static position from six (6) meters - STLK, Shooting from the center from a static position from six (6) meters - STC and Shooting from the right-wing from a static position from six (6) meters - STDK. The canonical correlation analysis obtained a significant and homogeneous structure of the connection between the set of motor abilities and the set of performing the technical elements of shooting on goal in a water polo game. It has been shown that there is no high ability of precision when shooting and that more attention should be paid to the training process of precision in water polo players who are aged 12 to 14 years.